Toward a knowledge economy: Factors affecting the sustainable consumption behavior in the Chinese online education industry - Pu, Ruihui; Jiang, Songyu; Dong, Rebecca Kechen; Chankoson, Thitinan; Supanut, Adul; Romprasert, Suppanunta; Tanamee, Danai (Frontiers in Psychology, 2022)
Buoyed by recent calls for researching and advancing the knowledge economy and sustainable development. This study introduces that the role of knowledge economy within the influencing covid-19 pandemic has emerged ample opportunities towards E-learning or online education industry worldwide. Knowledge sharing behavior has hugely driven by various sharing platforms concerning a newly paradigm for diversifying the education and learning. However, our study is to further extend the understandings and examine the related empirically correlations to deepen the online education for Sustainable Development (OESD). Both advancing theoretical underpinnings and enhancing the online education industry are highly integrated and introduced toward a sustainable pathway. This study brings the perspectives from consumer value, social identity social exchange and value-attitude-behavior to explain sustainable consumption behavior (SCBOEI) in the Chinese online education industry. Thus, the relationship among factors in this study are statistically examined and the SCBOEI model as the new theoretical insights is introduced in a way of sustainable consumption behaviors in Chinese online education industry. By end, this study addresses managerial implications to practitioners, the government, universities, and markets. Method: Employing a quantitative approach, about 559 valid questionnaire survey are collected from Chinese higher education institutions. This study is newly investigated participants from four controlling variables and six latent variables. The bootstrapping method was applied to validate mediating factors and their interacting relationships. The finding reveals that a set of classic psychological theories related fits to the SCBOEI in higher education from the consumer value, contextual factors, social identity, sustainable consumption attitudes, and consumer engagement to explain SCBOEI. The mediating role of identity, sustainable consumption attitudes, and consumer engagement are highly concerned. The value and contextual factors directly make impacts on SCBOEI through identity, sustainable consumption attitudes, and consumer engagement. The study significantly contributes to enriching the theoretical bases for advancing the literature on sustainable consumption behavior and online education. Our research provides managerial insights into government policy about the online education industry and marketers to set more advertisements to wake awareness of SCBOEI.